The Ed.D. as Investment in Professional Development: Cultivating Practitioner Knowledge (LEARNing Landscapes, 2015)
As teacher educators and participants in the US-based Carnegie Project for the Education Doctorate (CPED) initiative to differentiate the Ed.D/Ph.D., we have programmatic commitments to the centrality of practitioner knowledge for shaping professional development. Through CPED, we structure opportunities for local educators to develop their professional practices within their graduate studies toward an Ed.D, while maintaining full-time educational work commitments. Concurrently, we examine and document how CPED creates room, alongside concrete practice, to cultivate, promote, and value the voices, sensibilities, and capacities of practitioners engaged in advanced practices. In doing so, we confront marginalization of practitioners’ perspectives in the field and seek conditions and supports that insist on educators’ primary role in the complex project of education worldwide.
Keywords: professional development; practice; practitioner knowledge